ASSESSMENT OF FIELD DENSITY TESTS AND COMPACTION CHARACTERISTICS OF SOIL ON PADALARANG - CILEUNYI TOLL ROAD PROJECT - Utoyo Moeno, Hadi
ASSESSMENT OF FIELD COMPACTION TESTS AND COMPACTION CHARACTERISTICS OF SOIL ON PADALARANG-CILEUNYI TOLL ROAD PROJECT, Nadi U Moeno, 1909, Program Sistem dan Teknik Jalan Raya, Fakultas Pasca Sariana, Institut Teknologi Bandung. Comparisons between strength, density, moisture content and classification properties of a tropical residual soil used to form the embankment of the Padalarang-Cileunyi Toll Road, Bandung, have been made. Field tests carried out included use of the Dynamic Cone Penetrometer to assess subgrade strength, and both nuclear and sand cone procedures to evaluate in situ density and moisture content. The complementary laboratory programme included compaction, CBR and Atterberg Limit testing. Field testing was carried out at 51 locations, the soil at these locations then being taken back to the laboratory for the complementary laboratory test programme. Bulk samples of soil were also taken beside the field test points. The comprehensive test programme found that there was a good correlation between DCP penetration values and CBR, the correlation, however, being slightly different from some published relationships. Comparison between the nuclear and sand cone evaluations of in situ density characteristics found a reasonably consistent correlation, with nuclear dry density values being generally slightly smaller than corresponding sand cone values. Bigger variations were found in moisture content for these high moisture content materials. This could make application of specifications difficult, without a suitable calibration relationship. However, in all cases satisfactory strength of in situ compacted material was found. The residual volcanic sources of soil used showed wide variations in compaction characteristics, even when taken from the one source. A family of compaction curves was derived, and is considered necessary in such varying circumstances in order to assess more accurately the relative compaction in the field, for which a wide variation was encountered. At high relative compaction the corresponding subgrade strength was very satisfactory, higher than might be considered for the soil category involved; this is a feature of such residual volcanic soils .